Factors influencing the development of STEM competencies in vocational training: an analytical review of international studies - I. N. Popova; A. I. Satdykov (Russian State Vocational Pedagogical University, 2024)
Introduction. The development of STEM competencies worldwide is a priority in contemporary scientific research. Despite its significance for modern advancements in this field, the factors influencing the formation of STEM competencies remain insufficiently explored and are only partially addressed in existing scientific literature. This gap underscores the relevance and timeliness of the current study. Aim. The present research aimed to systematise scientific concepts regarding STEM competencies and the conditions necessary for their development, which are essential for understanding the prospects of STEM advancement in vocational education. Methodology and research methods. The research is a review-analytical study that aims to reflect on both the theoretical and applied aspects of STEM education. This paper systematises scientific perspectives on the definitions and models for the development of STEM competencies. It analyses scientific articles published between 2005 and 2024, facilitating the construction of a system of factors that influence the development of STEM competencies within the context of vocational education in foreign countries. Results and scientific novelty. The authors systematically organised the factors and concepts related to the conditions necessary for the development of STEM competencies within the context of vocational training for the innovation economy. A comprehensive system of factors influencing STEM competencies was described, and the barriers that impede the advancement of this area have been identified. Practical significance. The findings of the study can be applied to the development of educational programmes for training specialists in critical and end-to-end technologies within the vocational training system.